Comparative in vitro estimates of inhalation toxicity of selected nanoparticles - Dhakal, Kiran (Kansas State University, 2009)
Airway inflammation is characterized by the release of pro-inflammatory cytokines (IL-6) and chemokine (IL-8) from airway epithelial cells. To screen for the potential inhalation toxicity as inflammation, we tested exposure of metal oxide nanoparticles (NPs)-Titanium dioxide, Magnesium oxide, FastAct and Titanium Silicon Oxide-Manganese (TSO-Mn)-Aerogel to BEAS 2B human bronchial epithelial cells. A monolayer of cells having 80 – 90% confluence was treated with different concentrations of the NPs and feedlot dust as positive control for inflammatory processes. Releases of IL-6 and IL-8 into the culture supernatant fluid were measured by sandwich enzyme-linked immunoassay (ELISA). Characterization of NPs such as solubility and agglomeration in cell culture media were carried out to predict the effect of these properties in cellular responses. Feedlot dust increased the release of both IL-6 and IL-8 by 3 to >5 fold, suggesting an inflammatory effect while NPs did not show any effect either at increasing the dose or duration of the incubation with cell. The NPs at higher doses reduced the total IL-6 and IL-8 released, suggesting that the NPs may have bound with the cytokine and chemokine or somehow interfered with their function. The inert activity of NPs was further investigated by inspecting cell morphology, counting viable cells and assessing mitochondrial membrane potential. Concentrations at 1000 mg/L of TiO2 and 250 mg/L TSO-Mn-Aerogel could apparently limit lung epithelial cell multiplication by partially occupying the intercellular spaces, qualitatively increasing the number of cell pores and resulting in less recovered cells after 12 hours of incubation. Cells exposed to feedlot dust and titanium NPs were less viable as indicated by propidium iodide staining, but cells exposed to TSO-Mn-aerogel were more apoptotic as indicated JC-1 staining. These changes occurred at projected inhalation exposure levels > 40-100 fold above the nuisance dust level for TiO2 and permissible exposure limit for Manganese. No MgO exposures reduced apparently recovered cells to < 50% as indicated by manual hemocytometer counts (+ 15-25% variability). The lack of toxicity was most likely reflected from the high MgO solubility in the incubating media, and the relative non-toxicity of MgO.
Keywords: Inhalation; Toxicity; Nanoparticle; Public health; Health Sciences, Public Health (0573)